Developing playwriting skills for fast learners in the intermediate level - Moscare, Eulanda A. (1974)
The study shows how to develop playwriting skills among the fast learners in the intermediate grades. It seeks to determine the objectives involved in developing playwriting skills in relation to the present educational goals as regards to teaching fast learners, the guiding principles in teaching playwriting skills to fast learners, the methods by which playwriting skills can be effectively taught to fast learners, and creative activities that are best suited to developing playwriting skills among fast learners.